GA-based dynamic survivable routing in WDM optical networks with shared backup paths - Le, Vinh Trong (VNU Journal of Science: Mathematics - Physics, 2007)
Abstract. This paper considers the problem of dynamic survivable routing in WDM networks with single link íailure model. This work mainly concems in how to dynamically đetermine a protection cycle (i.e., two link-disjoint paths between a node pair) to establish a dependable lightpath with backup paths sharing. The problem is identified as NP-complcte, thus a heuristic for fmding near optimal solution with reasonable computation timc is usually preferred. Inspired from the principle of genetic algorithms (GA), a GA-based survivable routing algorithm for the problcm with a new íìtness íunction, which allows us to improve blocking períormance, will be proposed. Extensive simulation results upon the ns-2 network simulator and two typical netvvork topologics show that our algorithm can achieve a signiíìcantly lower blocking probability than conventional algorithms.